Spread bancário: uma análise cross-country em mercados relevantes para o Banco Santander - Vanessa Fonseca Monteiro Elias (2011)
This work is a case study of Banco Santander S.A. The aim is to comparatively analyze the banking spread in a sample of six countries where businesses are most relevant to this bank. The countries are: Brazil, Mexico, Chile, Spain, Portugal and the United Kingdom. The focus is on Brazil. The data for the study were collected from annual financial statements (Balance Sheet and Statement of Income) and standardized by the International Financial Reporting Standards (IFRS). The time horizon covers the years 2005 to 2009. The analysis of the banking spread was performed from two related perspectives. The first one by a breakdown of the banking spread into its accounting components. After that, from an econometric study seeking to test the Keynesian hypothesis of liquidity preference in the sample countries over time. In the first part of the work, in which the spread was calculated in an "ex post" way, the results were in line with expectations. From the sample countries, Brazil was the one that showed the largest spread in average years, besides having the highest average in accounting components, except for the component "Profitability After Tax / Total Assets." This analysis also showed that among the sample countries, developed countries (Spain, Portugal and the UK) have the lowest spreads. In the second part of the work it was used the "Proxy" interest rate as the explanatory variable, and as the dependent variable, the spread found in the accounting decomposition in the first part of this work. The method used was the econometric technique "Panel Data". The statistical and econometric tests have shown that the model panel - Fixed Effects would be most appropriate for the data structure of this research. This result is expected, since this model captures the differences between units in the intercept, and this work investigates countries with economic and financial realities quite different. However, the liquidity preference hypothesis was not confirmed for this study, e.g. one can not say that there is a trade-off between profitability and liquidity to countries in the sample over time.